Kajian Pindah Panas Tungku Biomassa Dan Heat Exchanger Pada Alat Pengering Hybrid Berbahan Bakar Limbah Biomass: Heat Transfer Study on Biomass Furnace and Heat Exchanger of Biomass Waste Hybrid Type Dryer - Guyup Mahardhian Dwi Putra; Diah Ajeng Setiawati; Sri Hartini (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2015)
Objective of this research was to conduct performance test on additional heat system of Green House Effect (ERK) dryer type. Experimental research methodology was conducted by analyzing heat losses on wall furnaces, bottom of furnace, ventilation of furnace, and analyzing heat received by greenhouse from heat exchanger. The experimental result showed that the greatest heat losses occured on wall furnace as much as 79.41% and the drying process efficiency of furnace system and heat exchanger as much as 14.48%.